Segmental neurofibromatosis with compression of the spinal cord at the cervical level. Literature review and case report - D. A. Gulyaev; I. Yu. Belov; D. V. Nizolin; L. B. Mitrofanova; N. A. Primak; D. S. Godanyuk; I. A. Kurnosov (Сибирский онкологический журнал, 2022)
Background. Neurofibromatosis is a fairly rare disease (1/3000). In 1992, V. Riccardi described seven types of neurofibromatosis. Segmental neurofibromatosis (sh), also known as type V neurofibromatosis, is an extremely rare variant characterized by the development of typical cutaneous manifestations or one body segment neurofibromas. Clinical case. Currently, the literature describes about 100 cases of sh and only one of them with compression of the spinal cord. We present our first case of this nosological form with spinal cord compression in a Russian patient. A 70-year-old patient, due to an increasing paresis in the left extremities, underwent mri of the cervical spine, which revealed solid tumors located extramedullary intra-extradurally at the level of c2-c3 vertebrae with pronounced compression of the spinal cord. At the time of hospitalization, clinical presentation was characterized by deep spastic tetraparesis (1–2 points), impairment of all types of sensitivity from the c4 level by the conductive type, and dysfunction of the pelvic organs by the type of delay. Karnofsky index was 50 %, 2 points on the Fim scale. Standard c2-c3 vertebrae laminectomy was performed. Spinal cord compression was eliminated due to the removal of intradural tumors. Subsequently, extradural tumors were removed step by step. On histological examination, tumors were represented by intertwining bundles of elongated schwann cells with wavy nuclei with pointed ends and ileogenic fibers. Mucin present in the stroma separated cells and fibers. Conclusion. Sn is a rare type of neurofibromatosis. However, from the point of view of genetics, it is most likely incorrect to attribute it to a separate type of neurofibromatosis, since the cause of its development is mosaicism of somatic cells due to mutation of the NF 1 gene. Sn is rarely manifested by the development of spinal nerves multiple neurofibromas, however, it can be accompanied by a gross neurological deficit caused by compression of the spinal cord such neurofibromas. Surgical treatment is based on basic and special surgical principles that determine the anatomical and morphological characteristics of the area of intervention, the compliance of which allows for good treatment results.